ICP27 Selectively Regulates the Cytoplasmic Localization of a Subset of Viral Transcripts in Herpes Simplex Virus Type 1-Infected Cells - Pearson, Angela (American Society for Microbiology, 2004)
Evidence suggests that the herpes simplex virus regulatory protein ICP27 mediates the nuclear export of viral transcripts; however, the extent of this activity during infection is unclear. ICP27 is required for efficient expression of the long, leaky-late UL24 transcripts, but not for that of the short, early UL24 transcripts. We found that infection by an ICP27-null mutant resulted in undetectable UL24 protein expression, which represented at least a 70-fold decrease relative to that of wild-type virus. Because lack of ICP27 had a greater effect on levels of UL24 protein than on transcripts, we examined its effect on subcellular localization of UL24 transcripts. In wild-type-infected cells, both short and long UL24 transcripts fractionated predominantly with the cytoplasm. However, in the absence of ICP27, greater than 50% of long UL24 transcripts were nuclear, while the percentage of short UL24 transcripts that were cytoplasmic was not reduced. These results also imply that the short UL24 transcripts are translated poorly. The effect of ICP27 on cytoplasmic localization of the long UL24 transcripts did not extend to other transcripts with which it shared a common 3′ end or to other transcripts tested, including gC and UL42, whose overall expression is highly dependent on ICP27. Thus, the dual effects of ICP27 on mRNA accumulation and cytoplasmic localization are not always linked. These results identify viral transcripts that are dependent on ICP27 for efficient cytoplasmic localization during infection, but they also indicate the existence of ICP27-independent nuclear export pathways that are accessible to many viral transcripts during infection.